2010
DOI: 10.1002/yea.1823
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism regulates H2S and SO2 production in Saccharomyces cerevisiae

Abstract: Sulfite (SO 2 ) plays an important role in flavour stability in alcoholic beverages, whereas hydrogen sulfide (H 2 S) has an undesirable aroma. To discover the cellular processes that control SO 2 and H 2 S production, we screened a library of Saccharomyces cerevisiae deletion mutants. Deletion of 12 genes led to increased H 2 S productivity. Ten of these genes are known to be involved in sulfur-containing amino acid metabolism, whereas UBI4 functions in the ubiquitin-proteasome system and SKP2 encodes an F-bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
(45 reference statements)
0
12
0
Order By: Relevance
“…Since downregulation of genes involved in cysteine, methionine, and threonine metabolism in the mixed cultures did not coincide with different concentrations of these amino acids relative to those of the pure cultures, it is unlikely to reflect a direct cross-feeding of these amino acids from the yeast to the bacterium. Alternatively, the downregulation of genes involved in synthesis of sulfur-containing amino acids might, for example, reflect a release of other reduced sulfur compounds (e.g., sulfide or sulfite [63]) by the yeast. The differential regulation of these genes in Lb.…”
Section: Discussionmentioning
confidence: 99%
“…Since downregulation of genes involved in cysteine, methionine, and threonine metabolism in the mixed cultures did not coincide with different concentrations of these amino acids relative to those of the pure cultures, it is unlikely to reflect a direct cross-feeding of these amino acids from the yeast to the bacterium. Alternatively, the downregulation of genes involved in synthesis of sulfur-containing amino acids might, for example, reflect a release of other reduced sulfur compounds (e.g., sulfide or sulfite [63]) by the yeast. The differential regulation of these genes in Lb.…”
Section: Discussionmentioning
confidence: 99%
“…The function of Ubi4 has been well explored in various yeasts. Deletion of ubi4 in S. cerevisiae may result in increased sensitivity to oxidative stress, apoptotic phenotype and shortened lifespan (Zhao et al ., ) as well as induced H 2 S production (Yoshida et al ., ). Ubi4 is important for an integrity of spindle pole bodies at meiotic stage of fission yeast (Okazaki et al ., ) and essential for stress tolerance and improved fermentation during ethanol production of wine yeast (Wu et al ., ; Peter et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, Natarjan et al [ 16 ] showed that several genes of sulfur metabolism are also controlled by GCN4 , which regulates the transcriptional activity of genes involved in amino acid synthesis either directly ( MET16 and MET25 ) or indirectly ( SUL1 , SUL2 , MET3 , MET14 , MET10 , MET1 , MET25 , MET6 , MET2 , MET28 and MET4 ). In addition, Yoshida et al [ 17 ] identified a new mechanism involving the F-box protein skp2p, which forms part of a complex, SCF SKP2 , which controls the stability of Met14p, and regulates the transcription of the STR1 , 2 and 4 genes.…”
Section: Introductionmentioning
confidence: 99%